The role of mangroves in supporting ports and the shipping industry to reduce emissions and water pollution - Pham, H.T.; Ngô, V.T.; Pham Thu Thuy; Bùi, T.T.; Nguyễn Thị, L.G. (Center for International Forestry Research, 2022)
This report provides scientific evidence on the role of mangroves in absorbing greenhouse gases and improving water quality through analysis of monitoring data relating to the water environment in Saigon River (Ho Chi Minh City), greenhouse gas emissions from Ho Chi Minh City seaports, and greenhouse gas sequestration in Can Gio mangrove forest (Ho Chi Minh City). This document presents, for the first time, comparative results of water quality indices for 2010–2020, at monitoring points in different areas including metropolitan, seaport, mangrove forest and open coast. A correlation between carbon emissions from seaports, and the amount of carbon absorbed by mangroves in Ho Chi Minh City, was also analysed for the first time. Our findings confirmed that mangroves can support the maritime industry to reduce greenhouse gas emissions and protect the environment. These findings can assist policymakers to identify those who can financially contribute towards the environmental services that mangroves provide, enabling the effective implementation of policy around payment for forest environmental services. We also highlight the need to have further specific studies, in other areas of the country, in order to build a complete database of the ecosystem services provided by mangroves in Vietnam.